2023
DOI: 10.1038/s41598-023-36730-z
|View full text |Cite
|
Sign up to set email alerts
|

Population size in QTL detection using quantile regression in genome-wide association studies

Abstract: The aim of this study was to evaluate the performance of Quantile Regression (QR) in Genome-Wide Association Studies (GWAS) regarding the ability to detect QTLs (Quantitative Trait Locus) associated with phenotypic traits of interest, considering different population sizes. For this, simulated data was used, with traits of different levels of heritability (0.30 and 0.50), and controlled by 3 and 100 QTLs. Populations of 1,000 to 200 individuals were defined, with a random reduction of 100 individuals for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The present study identified few markers trait associations but using higher number of landraces with diverse population and reference genome of the bambara groundnut would lead to detection of higher number of MTAs. The effect of population size on GWAS has been noted and the detection power of MTAs decreased according to reduction of population size [ 78 ]. Alqudah et al [ 22 ] reported that a range of 100 to 500 genotypes are suitable for performing GWAS and the selection genotype population should consider the genetic background, genotypic and phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study identified few markers trait associations but using higher number of landraces with diverse population and reference genome of the bambara groundnut would lead to detection of higher number of MTAs. The effect of population size on GWAS has been noted and the detection power of MTAs decreased according to reduction of population size [ 78 ]. Alqudah et al [ 22 ] reported that a range of 100 to 500 genotypes are suitable for performing GWAS and the selection genotype population should consider the genetic background, genotypic and phenotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Alqudah et al [ 22 ] reported that a range of 100 to 500 genotypes are suitable for performing GWAS and the selection genotype population should consider the genetic background, genotypic and phenotypic variation. Although, population size affects power of GWAS [ 78 ], but the result of the present study should be considered early evidence about the genomic regions and markers associated with the study traits and should be further validated using higher number of genotypes in more diverse environments.…”
Section: Discussionmentioning
confidence: 99%